Greywater Treatment Using Umbrella Sedge Plants and Activated Carbon Media with Constructed Wetland System - Azhari, Nadya Aulia; Sumiyati, Sri; Zaman, Badrus; Hardyanti, Nurandani; Prayoga, Surya (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Increased domestic wastewater discharge degrades river quality. This study evaluated phytoremediation using constructed wetlands with umbrella sedge plants to treat greywater prior to river discharge. Using a randomized block design, the study tested two substrates (activated carbon and quartz sand), plant quantity (0, 4, 8, or 12 clumps), and retention time (0 to 4 days) on key wastewater parameters: BOD, COD, TSS, ammonia (NH₃-N), and orthophosphate (PO₄). Data were analyzed via t-tests, ANOVA, and regression at a 5% significance level. Results indicated that a combination of activated carbon, 12 plant clumps, and a four-day retention time was the most effective in reducing TSS, BOD, COD, and phosphate, although it was less effective for ammonia. By the fourth day, all treated pollutant levels successfully met quality standards, making the water safe for river release.